Evaluation of dissolved heavy metals in water of the Sungai Semenyih (Peninsular Malaysia) using environmetric methods - Fawaz Al-Badaii,; Azhar Abdul Halim,; Mohammad Shuhaimi-Othman, (Universiti Kebangsaan Malaysia, 2016)
The study to determine the concentrations of dissolved heavy metals in the Sungai Semenyih and to use the environmetric methods to evaluate the influence of different pollution sources on heavy metals concentrations was carried out. Cluster analysis (CA) classified 8 sampling stations into two clusters based on the similarity of sampling stations characteristics, cluster 1 included stations 1, 2, 3 and 4 (low pollution area), whereas cluster 2 comprised of stations 5, 6, 7 and 8 (high pollution area). Principal component analysis (PCA) of the two datasets yield two factors for low pollution area and three factors for the high pollution area at Eigenvalues >1, representing 92.544% and 100% of the total variance in each heavy metals data sets and allowed to gather selected heavy metals based on the anthropogenic and lithologic sources of contamination.